The mediating role of parental satisfaction between marital satisfaction and perceived family burden among parents of children with psychiatric disorders. (January 2019) - Hasson-Ohayon, Ilanit; Ben-Pazi, Ayala; Silberg, Tamar; Pijnenborg, Gerdina H.M.; Goldzweig, Gil
Highlights: The hospitalization of a child with a psychiatric disorder is expected to challenge the parent's sense of efficacy as well as his/her sense of satisfaction. A mediating role of parental satisfaction between marital satisfaction and family burden was found. Longitudinal data is needed to confirm the presumed direction of effects which, if confirmed, suggest interventions in the marital domain. If effects occur in the opposite direction then intervening at the level of perceived burden (e.g., offering support) might be more beneficial. Abstract: Parents of children and adolescents with psychiatric disorders may experience perceived family burden. Although previous research has extensively addressed the contribution of clinical factors to perceived family burden, the contribution of marital and parental factors to family burden has rarely been studied in the context of parents whose children have a psychiatric disorder. The current study therefore examined the associations between marital satisfaction, parental satisfaction, parental efficacy, and perceived family burden among parents of children with psychiatric disorders (age range 5–14). Sixty-three parents of children who were hospitalized in a psychiatric hospital completed several questionnaires on marital satisfaction, parental satisfaction, parental efficacy, and perceived family burden. Results supported a mediating role of parental satisfaction (mediation effect size beta = −0.2, p < 0.05) but not parental efficacy (mediation effect size beta = 0.02, NS) between marital satisfaction and perceived family burden. Implications include the need to further study the parental experience during a child's psychiatric hospitalization and other possible factors related to burden. We would also recommend including family and marital therapy as part of routine care in this context.